A Critical Attitude to the Methodology and Analytical Logic of “The Islam of Sufis” - Rohullah Bahrami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“The Islam of Sufis” is the title of a book authored by the Tunisian writer, Mohammad Tayeb, on the Tasawwuf  and Irfan. Our purpose is not only to introduce and scrutinize the book but also to revise and criticize its contents. Therefore, characteristics such as general structure, outline, adjustment, publication, introductory aims and theoretical themes, discussions, conclusions, and cited references are addressed. Moreover, the author’s methodological approach and his analytical logic or reasoning, along with drawbacks of the work, are discussed. Methodologically, the hermeneutic approach of Sufism Islam, lack of paying attention to the geographic extension of Tasawwuf and the variety of Sufism movements, lack of genealogical and critical attitude to the origins of Sufism thoughts, and taking the Tasawwuf as a kind of Islamic religion (Sufism Islam) are the most notable criticized issues.